Coral calcifying fluid aragonite saturation states derived from Raman spectroscopy - DeCarlo, T.; D'Olivo, J.; Foster, T.; Holcomb, M.; Becker, Thomas; McCulloch, M. (Copernicus GmbH, 2017)
© 2017 Author. Quantifying the saturation state of aragonite (? Ar ) within the calcifying fluid of corals is critical for understanding their biomineralization process and sensitivity to environmental changes including ocean acidification. Recent advances in microscopy, microprobes, and isotope geochemistry enable the determination of calcifying fluid pH and [CO 2- 3 [, but direct quantification of ? Ar (where ? Ar D[CO 2- 3 ][Ca 2+ =Ksp) has proved elusive. Here we test a new technique for deriving ? Ar based on Raman spectroscopy. First, we analysed abiogenic aragonite crystals precipitated under a range of ? Ar from 10 to 34, and we found a strong dependence of Raman peak width on ? Ar with no significant effects of other factors including pH, Mg=Ca partitioning, and temperature. Validation of our Raman technique for corals is difficult because there are presently no direct measurements of calcifying fluid ? Ar available for comparison. However, Raman analysis of the international coral standard JCp-1 produced ? Ar of 12.3±0.3, which we demonstrate is consistent with published skeletal Mg=Ca, Sr=Ca, B=Ca,d 11 B, andd 44 Ca data. Raman measurements are rapid (=1 s), high-resolution (=1µm), precise (derived ? Ar ±1 to 2 per spectrum depending on instrument configuration), accurate (±2 if ? Ar < 20), and require minimal sample preparation, making the technique well suited for testing the sensitivity of coral calcifying fluid ? Ar to ocean acidification and warming using samples from natural and laboratory settings. To demonstrate this, we also show a high-resolution time series of? Ar over multiple years of growth in a Porites skeleton from the Great Barrier Reef, and we evaluate the response of ? Ar in juvenile Acropora cultured under elevated CO 2 and temperature.